(untitled) (Bangladesh Journal of Medicine, 2025)
Type 2 diabetes mellitus (T2DM) poses a considerable challenge to global health, with its incidence rising sharply, especially in low- and middle-income countries (LMICs). Epidemiological evidence indicates that T2DM constitutes more than 90% of all diabetes cases globally, influenced by factors such as urbanisation, an aging demographic, sedentary lifestyles, and changes in dietary habits. While high-income nations are experiencing a stabilisation in incidence rates, LMICs are witnessing an unprecedented surge, exacerbated by inadequate healthcare systems and unequal access to medical services. The management of T2DM is obstructed by various barriers, including socioeconomic inequalities, difficulties in adhering to lifestyle modifications and treatment regimens, and systemic shortcomings like inadequate screening processes and a shortage of trained healthcare professionals. These challenges not only hinder early detection but also worsen complications, leading to increased morbidity and healthcare expenditures. Nevertheless, progress in pharmacological and technological fields provides a glimmer of hope. Global initiatives, such as the WHO Global Diabetes Compact, stress the importance of collaborative efforts to improve prevention and management strategies. Tackling T2DM necessitates a holistic approach that includes healthcare reforms, the integration of technology, and international cooperation. This review analyses the worldwide trends associated with T2DM, highlights significant obstacles to effective management, and investigates new strategies aimed at alleviating its effects. Bangladesh J Medicine 2025; 36(2): 92-98